Blood biochemical parameters during early post-partum period of Surti buffalo in relation to placental expulsion time - PATHAK, M M; SARVAIYA, N P; TIWARI, S R (The Indian Journal of Animal Reproduction, 2023)
Thirty healthy and normal Surti buffaloes of research farm were selected and put into three groups after parturitionbased on their placental expulsion time; Group-I -less than 5 hr: Group-II - 8 to IO hr and Group-Ill - more than 12 hr. Blaodsamples were collected from jugular vein, starting immediately after parturition till complete expulsion of placenta at an intervalofone hour. Average concentration of Protein in three groups was 7.83, 9.05 and 9.66 gm/I 00ml, respectively. Whereas, averageconcentration for total and free cholesterol was 133.18, 150.90 and 154.15 and 7.19, 9.77 and 9.82 mg/I 00ml, respectively.Disturbed Ca: P ratio because of significantly lower level of phosphorus; may be one of the factor in delayed placental expulsionin buffaloes.
Keywords: Surti Buffalo; placental expulsion